(untitled) (Bangladesh Journal of Child Health, 2021)
Over the last few years, there is a rise in the use of button batteries(BB) in children’s toys and home appliances. Easy availability and small size of these batteries pose a significant risk of ingestion by small children which is exceedingly dangerous. After ingestion, the BB may lodge in the esophagus or enters easily into the stomach due to its variable sizes. If lodged in the esophagus, BB can cause injury due to their caustic and electric properties, as well as by direct pressure. In our case, the 16 months old boy had accidentally ingested a BB, removed approximately after 30 hours from the esophagus, had developed esophageal perforation followed by tracheaesophageal fistula, complications related to aspiration and finally expired due to bronchopneumonia with septicemia and respiratory failure. So, Prompt removal is mandatory to reduce devastating outcome if it is a button battery BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 41-44